Modeling of a cracked and repaired Al 2024T3 aircraft plate: effect of the composite patch shape on the repair performance: Effect of the composite patch shape on the repair performance. (Fracture and Structural Integrity, 2019)
In this work the finite element method was used to analyse the composite patch shape effect of the repair performance. Unlike all the works done conducted so far in this domain, this work proposed here, takes into account the reducing both, the stress intensity factor in repairing crack heads and the maximum shear stresses in the adhesive layer. This is the originality of this work. In function of the surface and the volume of the rectangular patch, three cases were taken into consideration: with conservation of the patches surface and its volume, with a reduction of the patches surface and its volumes, and in the end, with a reduction of the patches surface and conservation of its volume. The obtained results show that in the first case, the patch shape have no effect on the SIF, the sharp edges (obtuse, right and acute) of oblique shapes generate high shear stresses, in the second case, the reduced surfaces lead to significant mass gain with the same SIF values. and to an increase in the maximum shear stresses, in the latter case the patches shapes lead to a reduction of the SIF and the shear stresses.
Keywords: Patch; Composite; SIF; Stress; Shape; Adhesive; Crack